How Openness Enriches the Environment: Read More - Trapp, Stefanie; Ziegler, Matthias (Frontiers in Psychology, 2019)
The recently proposed OFCI model and specifically the Environmental Enrichment Hypothesis state that Openness positively influences the development of cognitive abilities (Ziegler, Danay, Heene, Asendorpf, & Bühner, 2012). It is assumed that Openness leads to engagement in more learning activities through creating an enriched environment (e.g. reading). However, despite positive evaluations of the OFCI model in general, there is little empirical research on this specific hypothesis. The current paper used a longitudinal design to test the positive impact of Openness on the frequency of reading activities in general and in the specific case of periods of unemployment. PIAAC (Programme for the International Assessment of Adult Competencies) data were used to fit structural equation models. The results show that Openness fosters greater engagement in reading activities over 3 years; a buffering function in case of unemployment could not be found. Theoretical and practical implications are discussed.